Daily Mail Postcard - The main street of Combles - Auteur inconnu (Wikimedia Commons, 1916)
Carte postale ancienne issue de Wikimedia Commons. Titre: Daily Mail Postcard - The main street of Combles. World War I Daily Mail Official War Photograph, Series 21, No. 162, titled "The main street of Combles (captured September 26thm 1916)". The obverse carries the following information: "Passed by Censor" and "'Combles is No longer a village, it is a shambles,' was remarked when it fell to British and French forces in co-operation".
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Carte postale